Reduced exposure variability of the CYP3A substrate simvastatin by dose individualization to CYP3A activity - Stoll, Felicitas E.; Burhenne, Jürgen; Lausecker, Berthold; Weiß, Johanna; Thomsen, Torben; Haefeli, Walter E.; Mikus, Gerd (Journal of clinical pharmacology, 2013)
This study aimed to demonstrate that the dose of a CYP3A substrate (simvastatin) can be adapted individually on the basis of CYP3A activity as assessed by midazolam metabolic clearance. In 18 healthy participants individual CYP3A activity was quantified using midazolam metabolic clearance both alone and during CYP3A inhibition with 40 mg ritonavir. Thereafter, simvastatin acid exposure was determined after a simvastatin standard dose (40 mg) and doses adapted to individual CYP3A activity at baseline and during CYP3A inhibition. Interindividual variability of CYP3A activity and simvastatin acid AUC0-24 was large and both correlated (r2 = 0.745, P < .001). The adapted simvastatin doses ranged from 25 to 80 mg and their administration reduced simvastatin variability fivefold. Despite the low adapted simvastatin dose of 12 mg during CYP3A inhibition with ritonavir, exposure increased (point estimate of 4.2 [90% CI: 3.15-5.61]) probably caused by additional OATP1B1 inhibition. CYP3A activity-based dose adaptation can be used to reduce interindividual variability in simvastatin exposure.